ANALISIS PENGARUH SISTEM KOMPENSASI DAN SISTEM ANGGARAN TERHADAP KINERJA PEGAWAI (STUDI KASUS DI BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN DAERAH KABUPATEN PACITAN) - Sulastiningsih -; Sri Mintowati (Universitas Sarjanawiyata Tamansiswa, 2022)
This research aims to analyze the effect of the compensation and budget system on the performance of the Pacitan Regency Education and Training Agency employees. This research used data analysis methods with several tests including data validity and reliabiliti test, classical assumption test and regression test. The data used were obtained from the distribution of questionnaires which were filled in by 34 respondents. The analysis showed that partially the budget system affects the employee performance in a positive significant movement with a t-count value of 3.640 and a significant level of 0.001. Similarly, compensation system also has a significant positive relation with employee performance in the number of 2.643 t value and 0.012 significant level. The budget and compensation system simultaneously affect performance employee with the bond value of 44.4 percent and the other remaining 55.6 percent is influenced by other factors outside of this study.